2014
DOI: 10.3791/51905
|View full text |Cite
|
Sign up to set email alerts
|

Using the Threat Probability Task to Assess Anxiety and Fear During Uncertain and Certain Threat

Abstract: Fear of certain threat and anxiety about uncertain threat are distinct emotions with unique behavioral, cognitive-attentional, and neuroanatomical components. Both anxiety and fear can be studied in the laboratory by measuring the potentiation of the startle reflex. The startle reflex is a defensive reflex that is potentiated when an organism is threatened and the need for defense is high. The startle reflex is assessed via electromyography (EMG) in the orbicularis oculi muscle elicited by brief, intense, burs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 51 publications
3
53
0
Order By: Relevance
“…To control for individual differences in shock sensitivity, we measured participants’ subjective tolerance using standard procedures from our laboratory (Bradford, Curtin, & Piper, ; Bradford, Magruder, Korhumel, & Curtin, ; Hogle et al, ). Participants rated a series of 200‐ms electric shocks of increasing intensity (7 mA maximum) administered to the distal phalanges of the second and fourth finger of the right hand.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To control for individual differences in shock sensitivity, we measured participants’ subjective tolerance using standard procedures from our laboratory (Bradford, Curtin, & Piper, ; Bradford, Magruder, Korhumel, & Curtin, ; Hogle et al, ). Participants rated a series of 200‐ms electric shocks of increasing intensity (7 mA maximum) administered to the distal phalanges of the second and fourth finger of the right hand.…”
Section: Methodsmentioning
confidence: 99%
“… We included mean general startle reactivity across both study visits (mean centered) as a covariate in the analyses of raw score startle potentiation/modulation measures to control for individual differences in raw startle response as recommended (Bradford, Kaye, & Curtin, ; Bradford, Magruder, Korhumel, & Curtin, ; Schmitz & Grillon, ). This covariate was unnecessary for standardized scores as the standardization procedure itself is designed to reduce individual differences.…”
mentioning
confidence: 99%
“…However, it does not seem that a greater number of shocks is always associated with greater startle blink responding. In fact, Bradford and colleagues (2014) showed that having more shocks (15) in a 100% probability condition produced less anticipatory startle responsivity than having fewer shocks (3) during a 20% probability condition with the number of trials held constant. These results, coupled with previous findings suggesting occurrence uncertainty and temporal uncertainty produce unique physiological and self-reported anxiety-related responses (Davies & Craske, 2015; Monat et al, 1972), suggest that the observed difference in startle responsivity between these two types of uncertainty is not due to the difference in the quantity of shocks.…”
Section: Discussionmentioning
confidence: 97%
“…Establishing the relative aversiveness of these various forms of uncertainty would inform understanding of the role each plays in the elicitation of physiological and subjective anxiety, as well as the development of both adaptive and maladaptive anxiety. A number of studies have experimentally manipulated the intensity and frequency of threat (Bradford, Magruder, Korhumel, & Curtin, 2014; Chin, Nelson, Jackson, & Hajcak, 2016; Dunsmoor, Bandettini, & Knight, 2007; Dunsmoor, Bandettini, & Knight, 2008; Hsu, Bhatt, Adolphs, Tranel, & Camerer, 2005; Marlin, Sullivan, Berk, & Miller, 1979; Monat, Averill, & Lazarus, 1972; Shankman et al, 2011; Williams et al, 2014). Shankman and colleagues (2011) found that temporal uncertainty and intensity uncertainty produced significantly larger startle responses than when the aversive stimulus was predictable in both conditions.…”
Section: Introductionmentioning
confidence: 99%
“…We conducted offline data processing using the PhysBox plugin (Curtin, 2011) within the EEGLAB toolbox (Delorme & Makeig, 2004) in MATLAB (The Math Works Inc., Natick, MA). We followed published guidelines for startle response reduction and processing (Blumenthal et al, 2005;Bradford, Magruder et al, 2014). Specifically, we high-pass filtered (4th order 28 Hz Butterworth filter), epoched (250-250 ms surrounding probe), rectified, and smoothed (4th order 30 Hz Butterworth low-pass filter) the data.…”
Section: Startle Response Measurementmentioning
confidence: 99%